Designing a pineapple machine - Zulkurnain bin, Salim (Universiti Malaysia Sarawak, UNIMAS, 2004)
The purpose of this study is to learn about the operation of pineapple machine and redesigned the new machine. To do this project, a few pineapple machines are studied to learn the main process of pineapple machine.